2018
DOI: 10.2166/nh.2018.074
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of terrestrial water storage anomalies in Northwest China during 1948–2002 using GRACE and GLDAS products

Abstract: Commencement of the Gravity Recovery and Climate Experiment (GRACE) provides an alternative way to monitor changes in terrestrial water storage (TWS) at large scales. However, GRACE dataset spans from 2002 to present, which greatly limits the application of GRACE data for long-term hydrological studies. Thus, the general linear model (GLM), random forest (RF), support vector machines (SVM), and artificial neural networks (ANN) methods were used to reconstruct the time series of terrestrial water storage anomal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…(4). A relaxed constraint is considered (Pellet et al, 2019): the WC budget is closed within an error r that follows a normal distribution with specified uncertainty (Yilmaz et al, 2011). The problem can be written in the following way:…”
Section: Water Cycle Budget Closure At the Basin Scalementioning
confidence: 99%
“…(4). A relaxed constraint is considered (Pellet et al, 2019): the WC budget is closed within an error r that follows a normal distribution with specified uncertainty (Yilmaz et al, 2011). The problem can be written in the following way:…”
Section: Water Cycle Budget Closure At the Basin Scalementioning
confidence: 99%
“…The cross-test proved that the water storage observed by gravity satellite was an efficient and reliable data supplement, which provided a way to monitor and manage water storage on a large scale. Although some studies indicated that SMS is a traditional and widely used indicator of water storage [44], it was obvious that SMS was not sufficient to reflect the changing pattern of water storage on a large scale. For example, Rodell et al (2009) reported that the Indian subcontinent experienced rapid depletion of water storage due to excessive pumping over the past decade [1], GRACE-based TWS sensitively observed a decline in water storage, while SMS did not detect this.…”
Section: Water Storage Changes Aggravate the Spatial Heterogeneity Of Water Resourcesmentioning
confidence: 99%
“…Therefore, the increasing water supply and the underlying surface of the forest ecosystem provided a clear SC water storage increase during 2003-2016. In particular, some large-scale water conservancy projects may also lead to the surplus of regional water storage [44]; therefore, the construction of reservoirs and wetlands is also a reason for the obvious raise of TWS. To sum up, the decreases in TWS in NC were mainly driven by human activities, while the decreases in SC were mainly driven by climate factors.…”
Section: The Dominant Driver Is Different Across East Asian Monsoon Areasmentioning
confidence: 99%
“…In this research, we used level-three data provided by CSR [24] in the form of grid data product, which has undergone a series of processing, such as gaussian smoothing, destriping filter, glacier isostatic adjustment (GIA), and the anomalies relative has been deducted by default to 2004 to 2009 time-mean baseline. The total water storage should be multiplied the scaling factors to restore much of the energy removed by processing [30,37]. Total water storage of this product has a high accuracy and it is suitable to be applied in the research area of this study [49,51].…”
Section: Grace Twsmentioning
confidence: 99%
“…Ning et al [28] used the water balance equation of TWS to carry out the statistical downscaling method, which indicated that TWS is comprehensively affected by precipitation, evapotranspiration, runoff, and other hydrological factors. Yang et al [37] used linear regression and machine learning models to reconstruct the total water storage anomalies in Northwest China during 1948-2002 while using GRACE and GLDAS products, indicating that TWS is closely related to soil moisture, snow water equivalent, and canopy water. Therefore, in this study, we selected six modeling factors, including precipitation (P), evapotranspiration (ET), runoff, soil moisture (SM), snow water equivalent (SWE) and canopy water (CW), and analyzed four kinds of machine learning methods: such as random forest (RF) [38], support vector machine (SVR) [39], artificial neural network (ANN) [40], and multiple linear regression (MLR) [41] to conduct a downscaling study on the GRACE-derived TWS and GWS in the long time series.…”
Section: Introductionmentioning
confidence: 99%